Synthesis, Characterization and Evaluation Antimicrobial Activity of Some New substituted 2-Mercapto-3-Phenyl-4(3H)-Quinazolinone - Al-Khuzaie, Mohammed; Al-Majidi, Suaad (Iraqi Journal of Science, 2023)
This work includes synthesis of new heterocyclic derivatives of 2-mercpto-3-phenyl-4(3H)-quinazolinone bearing 1, 2, 4-triazole and acetylenic amines moieties by using two ways. The first way includes reaction of 2-mercpto-3-phenyl-4(3H)-quinazolinone (1) with ethyl-2-bromopropanoate in methanol as solvent to gives ester derivative (2). Then, compound (2) was converted to (hydrazide, simecarbazid, phenylsimecarbazide and thiosimecarbazide) derivatives through its reactions with (hydrazine hydrate, simecarbazid, phenylsimecarbazide and thiosimecarbazide) respectively to give compounds (3-6). Finally, the cyclization of compounds (4-6) in alkaline media (4N-NaOH) gave the corresponding substituted triazole derivatives (7-9) respectively. While, compound (3) reacted with CS2 in alkaline media (20%KOH) to gives compound (10) that reacted directly with hydrazine hydrate to gives compound (11). The second way includes reaction of compound (1) with propargylbromide to gives compound (12). Then, compound (12) reacted with different secondary amines (by Mannich reaction) to give compounds (13 a-m). The structure of newly synthesized compounds were identified by spectral methods their [FTIR and some of them by 1HNMR, 13C-NMR] and measurements some of its physical properties and some specific reactions. Furthermore were studied the effects of the preparing compounds on some strains of bacteria and fungicidal.